Mining the characteristics of the binding pocket in druggable and undruggable proteins to foster innovative drug design - Gomes, Bruno Filipe Andrade (2022)
Tese de mestrado, Química Medicinal e Biofarmacêutica, 2022, Universidade de Lisboa, Faculdade de Farmácia.